006.89 PRINCIPLES OF CLASSIFICATION OF COSTS TO ENSURE PRODUCT QUALITY IN PRODUCTION - Xolboyeva, Shoxsanam; Kosimov, Ahtam (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
This article about the development of methods for optimizing quality costs in production enterprises in a market-oriented management system, ensuring product quality in the production process and choosing the right types of costs.